2011
DOI: 10.1007/s12028-011-9595-7
|View full text |Cite
|
Sign up to set email alerts
|

SAH Pituitary Adrenal Dysfunction

Abstract: Disruption of the hypothalamic-pituitary-adrenal axis may occur after aneurysmal subarachnoid hemorrhage, resulting in hypopituitarism. An electronic literature search was conducted to identify articles with English-language abstracts published between 1980 and March 2011 that addressed hypothalamic-pituitary-adrenal axis insufficiency and hormone replacement. A total of 18 observational and prospective, randomized studies were selected for this review. Limited data are available evaluating pituitary effects d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Poll et al has found that patients with normal diurnal serum free cortisol measurement had a significantly shorter intensive care unit-stay, less complications and more favorable outcome [18] (Table 2). However, the empirical glucocorticoid replacement which is not based on the presence of documented acute HPA axis dysfunction may be harmful or, at best, ineffective [43].…”
Section: Impact Of Neuroendocrine Changes On Outcome Of the Patientmentioning
confidence: 99%
“…Poll et al has found that patients with normal diurnal serum free cortisol measurement had a significantly shorter intensive care unit-stay, less complications and more favorable outcome [18] (Table 2). However, the empirical glucocorticoid replacement which is not based on the presence of documented acute HPA axis dysfunction may be harmful or, at best, ineffective [43].…”
Section: Impact Of Neuroendocrine Changes On Outcome Of the Patientmentioning
confidence: 99%